ANALISIS PERANAN DINAS PERINDUSTRIAN DAN PERDAGANGAN DALAM PENGEMBANGAN INDUSTRI KECIL DI KOTA MEDAN - Rizki Arif Putra; M. Arif Nasution; Agus Suriadi (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2021)
At a time when banking is facing difficulties to make the debtor which is not problematic, UMK became an alternative credit channeling of banking. There is little industry in the city of Medan have a very strategic role, both in the Equalization of opportunities, equitable spread of the Interest of the industry that supports the development, employment equity, and aims to form indentations the Community industry is small, independent, tough, and developed into a major industry. This research aims to analyze the role of the Service industry and are experts in developing small industries in the city of Medan. This research uses descriptive qualitative approach method. Results of the study showed a number of productive activities performed by the Department of industry and experts and the weakness of the perpetrators of the small and medium industries to expand the network of ekternal.